Urban-Rural Discrepancy of Low Income Women’s Health Outcomes. - Abdul Kadir, Hazila; Wan Puteh, Sharifa Ezat (IIUM Medical Journal Malaysia, 2023)
Introduction: Malaysia's rapid economic growth and rising living costs significantly affect the lower-income population, which is defined as individuals earning less than MYR3,855.00 (USD892.26) per month (B40). The study aimed to ascertain the quality of life (QOL), the needs of B40 women living in urban and rural areas, and their health status. Materials and Methods: On the year 2020, a cross-sectional study was conducted. A total of 300 respondents from the rural and urban poor were questioned about their needs, health status, and QOL using semi-guided instruments such as the EuroQol 5 Dimension (EQ5D) and Visual Analogue Score (VAS). Bivariate and multivariate analyses were performed to identify factors influencing QOL and health status. Results: A total of 88% of respondents were Malays, 9.3% were Indian, and 2.7% were Chinese. The respondents' mean age was 45 years old. Most of the respondents were stay-at-home mothers (39.7%), employed (39.0%), and had completed secondary school education (61.0%). The average monthly household income was MYR1654.00 (SD845.3). Approximately 58.7% of respondents received subsistence assistance. A total of 47.7% of the respondents suffered chronic medical illness (hypertension, diabetes, hyperlipidemia, renal problems, asthma, heart disease and cancer). The respondents obtained services from government-funded clinics or hospitals (86.0%) and private clinics or hospitals (14.0%). Most women sought treatment as inpatients at government hospitals (89.3%), while 10.7% sought care in private hospitals. A total of 94.0% paid for their own treatment, while 6.0% had their employers reimburse them. The respondents did not suggest any insurance benefits, particularly pertinent to the current government. Conclusion: The lack of chronic medical illnesses was one of the most crucial characteristics associated with high QOL and good health status.